2014
DOI: 10.1002/jctb.4371
|View full text |Cite
|
Sign up to set email alerts
|

Controlling pH in biological depuration of industrial wastewater to enable micropollutant removal using a further advanced oxidation process

Abstract: BACKGROUND: The accumulation of bicarbonates during the biological treatment of high organic strength wastewater has a negative impact on the remaining micropollutant removal through chemical oxidation due to its scavenging effect on hydroxyl radicals. In this study, a lab-scale sequencing batch reactor (SBR) was operated at circumneutral pH to avoid inorganic carbon accumulation, followed by Fenton and photo-Fenton processes to treat an agro-food industrial effluent with acetamiprid as a model pollutant at 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…They were detected in the wastewater as a result of the cleaning step applied to the fruits and vegetables processed. Amongst them, ACTM, a neonicotinoid insecticide, despite not being the most abundant (only 0.5 μg L −1 vs 3.3 μg L −1 of TBZ), is one of the most persistent (owing to its low reactivity in further chemical treatments) [13].…”
Section: Gazpacho Wf Accountingmentioning
confidence: 99%
“…They were detected in the wastewater as a result of the cleaning step applied to the fruits and vegetables processed. Amongst them, ACTM, a neonicotinoid insecticide, despite not being the most abundant (only 0.5 μg L −1 vs 3.3 μg L −1 of TBZ), is one of the most persistent (owing to its low reactivity in further chemical treatments) [13].…”
Section: Gazpacho Wf Accountingmentioning
confidence: 99%
“…This situation requires the development of alternative remediation technologies to limit the discharge of these compounds in the environment. Numerous scientific studies were recently reported proving the effective removal of micropollutants contained in actual urban wastewater [38,39]. Membrane bioreactors technology (MBR) combining conventional activated sludge (CAS) treatment with a membrane filtration system was reported as an alternative to increase the effluent quality decreasing the membrane cost [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…The collection included in the present issue is not exhaustive, but reflects the most relevant aspects on the state of the art, and the excellent potential of new materials with photocatalytic properties (Fe 2 O 3 /Al 2 O 3 , TiO 2 ‐SiO 2, iron on montmorillonite composites, N‐doped TiO 2 /PS aerogels, iron loaded hydrogels), as well as electrochemical processes for wastewater treatment. The applications regarding the combination of AOPs with biotreatment, water disinfection and abatement of emerging and persistent aqueous contaminants show the diverse contributions of very efficient teams of biologists, engineers and chemists working together.…”
mentioning
confidence: 99%